Effect of photodynamic therapy on vaginal intraepithelial neoplasia grade one: A retrospective cohort study - Yao Yang; Dan Cao; Yi Chen; Ying Xu; Zhenhong Xiong; Zhengrong Zhang; Dan Wu (Photodiagnosis and Photodynamic Therapy)
Objective: To evaluate the efficacy of photodynamic therapy (PDT) for vaginal intraepithelial neoplasia grade 1 (VaIN1) related to high-risk (Hr)-human papillomavirus (HPV). Methods: Participants aged 25–65 years treated for VaIN1 between March 2022 and September 2022 were retrospectively analyzed into three groups. The PDT and follow-up groups were matched 1:1 for gravidity, HPV type, and quadrants involved. The PDT and CO2 laser groups were compared without matching. Patients were followed up at 6, 12, and 24 months. Results: After matched, the lesion and Hr-HPV clearance rates of the PDT group (89.5%, 89.5%, 92.1%, and 81.6%, 84.2%, 89.5%) were significantly higher than those of the follow-up group (31.6%, 50.0%, 63.2%, and 21.1%, 26.3%, 31.6%, P < 0.05) at 6, 12, and 24 months. But the lesion clearance rates did not differ significantly between the PDT (68.9%, 82.2%, and 91.1%) and CO2 laser groups (68.7%, 78.3%, and 85.5%, P > 0.05) at 6, 12, and 24 months, and so did Hr-HPV clearance rates (PDT as 62.2% and 77.8%, and CO2 laser 54.2% and 61.4%, respectively, P > 0.05) at 6 and 12 months. However, at 24 months, the Hr-HPV clearance rate was higher in the PDT group than in the CO2 laser group (86.7% vs 71.1%, P = 0.047). In the PDT group, none of the lesions progressed. Conclusions: Compared with CO2 laser, PDT resulted in a higher Hr-HPV clearance, as well as a low risk of complications and disease progression. PDT is an effective and noninvasive treatment for VaIN1.